先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a) 填空:当y=1时2y的平方+6y-先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a)填空:当y=1时2y的平方+6y-3y的平方
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 01:09:41
先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a) 填空:当y=1时2y的平方+6y-先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a)填空:当y=1时2y的平方+6y-3y的平方
先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a) 填空:当y=1时2y的平方+6y-
先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a)
填空:当y=1时2y的平方+6y-3y的平方-5y=?
打错了,是当y=-1时
先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a) 填空:当y=1时2y的平方+6y-先化简,再求值:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a)填空:当y=1时2y的平方+6y-3y的平方
:(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a)
=4a²-3a-2a²-a+a+2-a²+4a
=a²+a+2
2y的平方+6y-3y的平方-5y=-y²+y=-1+1=0
(4a的平方-3a)-(2a的平方+a-1)+(2-a的平方+4a)
=4a²-3a-2a²-a+1+2-a²+4a
=a²+1
填空:当y=1时2y的平方+6y-3y的平方-5y=?
2y的平方+6y-3y的平方-5y
=-y²+y
=-1+1
=0
(4a^2-3a)-(2a^2+a-1)+(2-a^2+4a)=(4-2-1)a^2+(-3-1+4)a+(1+2)=a^2+3
2y^2+6y-3y^2-5y=-y^2+y
当y=1时
2y^2+6y-3y^2-5y=-y^2+y=0
(4a^2-3a)-(2a^2+a-1)+(2-a^2+4a)=4a^2-3a-2a^2-a+1+2-a^2+4a=a^2+3.
2y^2+6y-3y^2-5y=-y^2+y,当y=1时,-y^2+y=-(1)^2+1=0